2000
DOI: 10.1093/njaf/17.3.95
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Three Pine Species after Eleven Years on Reclaimed Minesoils In Virginia

Abstract: A reforestation experiment was established to test the growth of three pine species on two different surface-mined sites in the Appalachian coalfields of southwest Virginia. One site was mined just prior to enactment of the 1977 Surface Mining Control and Reclamation Act (SMCRA), and one site was mined and reclaimed to its approximate original contour in accordance with post-SMCRA regulations. Three pine species (Pinus taeda, P. virginiana, and P. strobus) were planted on each site in 1981. A fertilization and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Additionally, competition for nutrients has been found to limit seedling survival and growth (Walker 2002;Thompson & Pitt 2003;Valdecantos et al 2006). Despite these deterrents, studies have shown that forests can be successfully restored on abandoned mine sites with productivity at least equal to that of native forests removed by mining (Torbert & Burger 1990;Torbert et al 2000;Rodrigue & Burger 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, competition for nutrients has been found to limit seedling survival and growth (Walker 2002;Thompson & Pitt 2003;Valdecantos et al 2006). Despite these deterrents, studies have shown that forests can be successfully restored on abandoned mine sites with productivity at least equal to that of native forests removed by mining (Torbert & Burger 1990;Torbert et al 2000;Rodrigue & Burger 2004).…”
Section: Introductionmentioning
confidence: 99%
“…White pine (Pinus strobus L.) has likely been the most extensively used species in reclamation. This species success in reclamation has ranged from good for a study in southwestern Virginia where the species averaged 58% survival and 3.8 m of height growth after 11 years (Torbert et al 2000) to poor for a study in southeastern Ohio where no pines survived after three years (Larson et al 1995).…”
Section: Executive Summarymentioning
confidence: 99%
“…Rodrique and Burger (2000) found that pre-SMRCA lands were as productive as the unmined condition in the Midwest but was less in the east. Torbert et al (2000) reported that white, Virginia, and loblolly pines grew significantly better on pre-SMRA sites that post-SMRA sites. The result of the post-SMRA is a forest that either is not established or grows at a rate that is economically feasible.…”
Section: Introductionmentioning
confidence: 98%